A social cognitive approach to understanding employee substance use: An example from the Philippines. (2nd October 2019) - Tiu, Reniel B.; Teng-Calleja, Mendiola; Hechanova, Ma. Regina M.; Go, Jaimee Felice C.
Abstract: Current studies on employee substance use suggest that external and internal factors explain employee substance use behavior. However, most studies fail to account for the possible relational dynamics between mental processes and the work environment. To address this gap, we conducted a study among work organizations in the Philippines to explore employee substance use using a social cognitive approach. Structural equation modeling (SEM) revealed that employee attitudes relating to drinking, smoking, and/or illicit drug use mediate the relationship between company culture and employee substance use, with the former influenced by other elements of the work environment. Implications to work organizations and human resource management practice are discussed.